Women's educational activism and higher education in Ireland, 1850-1912 - Walsh, John (Routledge, 2022)
Irish higher education in the mid-nineteenth century was designed to accommodate men of the upper and middle classes. The enduring strength of traditionalist Victorian social attitudes, dictating a separate and lesser role for women in society and the explicit relegation of women to the private and domestic setting, remained a formidable barrier to female participation in university education up to the early 1900s.1 The exclusion of women from university colleges was first challenged by Protestant activists and educators, while the early success of the Protestant women’s colleges and creation of the Royal University stimulated a substantial development of similar institutions for Catholic girls. A feminist campaign led by women graduates was crucial in securing the entry of women to the universities on the same basis as men in the early 1900s, not least because the women graduates succeeded in mobilising support on an inter-confessional basis.
Gender and History, Ireland 1852-1922
Keywords: Making Ireland; EDUCATION; Educational Reform